Perception of Indonesian Nursing Students Regarding Caring Behavior and Teaching Characteristics of Their Clinical Nursing Instructors - Madiha Mukhtar; Nursalam Nursalam; Ninuk Dian Kurniawati (Universitas Airlangga, 2016)
Student’s learning and performance reflects the professional attitude, behavior, ethics and standards of their instructors. The aim of this study is to analyse the perception of Indonesian Nursing students regarding caring behavior and teaching characteristics of their CNIs. In this exploratory cross-sectional study, 149 Professional Nursing students from Regular program (Baccalaureate) and Post diploma BSN and 15 Clinical Nursing Instructors were recruited from nursing faculty of public university located in Surabaya Indonesia. Data were collected by questionnaire and FGD was conducted to explore detailed information. In descriptive analysis: 6 % students perceived the caring behavior of their clinical instructors as low, 52.3% responds it as enough and 41.6 % considered it good. Teaching characteristics of CNI; 2.7% low, 26.8 as enough and 70.5 % good as perceived by their students. Data collected from students was analysed by using logistic regression test. Professional commitment with (P-value .038), motivation (P-value .010) and clinical placement environment (P-value .002) in main category (significance value is < 0.05) shows influence on perception of Indonesian nursing students regarding caring behaviour and teaching characteristics of their CNIs. In focused group discussion students’ recommended to increase the number of visits in clinical area and emphasises on bed side clinical demonstration. It can be concluded that students’ characteristics does have influence on their perception regarding caring behavior and clinical setting environment influence their perception regarding teaching characteristics of their CNIs.